Efficient space and resource planning strategies: treelike fractal traffic networks of the Ming Great Wall Military Defence System. Issue 1 (2nd January 2018) - Cao, Yingchun; Zhang, Yukun
ABSTRACT: Traditionally understood as a linear defence wall, the Great Wall in the Ming Dynasty (1368–1644) is actually part of a larger, complex system: the Ming Great Wall Military Defence System (the M-GWMDS).This article presents findings of an ongoing research into the authenticity of the M-GWMDS, based on the Geographic Information System (GIS) platform and fractal theory. Here, the focus is on the analysis of the spatial distribution characteristics of the traffic networks of the M-GWMDS, as this allows elucidating the system relationship of the M-GWMDS based on such characteristics. The study findings reveal that the M-GWMDS is thoroughly integrated with the linear Great Wall via the treelike fractal traffic networks, thus forming a defence system characterized by highly efficient space and resource planning. At the more macroscopic level, the Great Wall military defence settlement system and the civil settlement system are further merged into a mutually complementary double-fractal structure, which effectively copes with the special man–land relationship on the survival and defence in the border areas.